Improving Studentsâ Skills in Translation through Students-Teams Achievement Division (STAD) Technique - Ahmad, Syarwan (AT-TALIM, 2015)
This classroom action rresearch was aimed at improving studentsâ skills in translating at the English Department of the State Islamic University (UIN) Ar-Rarniry Banda Aceh by using the Student-Teams Achievement Division (STAD) Technique. Throughout the entire cycles, students worked in groups of 4-5 persons to plan and write their translations. The study showed that the average score of pre- test (66) increased dramatically to reach 86, and moved up a little higher (87) after the second cycle. It is recommended that STAD Cooperative Technique be implemented in teaching translation courses.Â Â Key words: Teaching translation; STAD; UIN Aceh.Copyright Â© 2015 by Al-Talim All right reserved